Awareness of diabetic retinopathy among diabetic patients - Amna Rizwan; Abu Sufyan; Asfandyar Asghar; Haamid Khan; Bilal Ahmad; Muhammad Hamza Rabbani (Journal of the Pakistan Medical Association, 2020)
Objectives: To assess the awareness of diabetic patients about diabetic retinopathy. Method: The cross-sectional study was conducted at the Ophthalmology Department, Fauji Foundation Hospital, Rawalpindi, Pakistan, from April 2018 to April 2019, and comprised diabetic patients of either gender aged 21-80 years. A pre-tested semi-structured questionnaire was used to collect data on socio-demographic, diabetes and diabetic retinopathy characteristics. Fundoscopic examination was done, and the presence and stage of diabetic retinopathy were documented. Data was analysed using SPSS 20. Results: Of the 132 subjects, 9(6.8%) were male and 123(93.2%) were females. The majority 64(48.5%) was aged 61-80 years. Overall, 74(56.1%) patients were aware that diabetes could affect their eyes, 57(43.2%) were never diagnosed with diabetic retinopathy, 76(57.6%) had gained information about diabetic retinopathyfrom ophthalmologists, 61(46.2%) and 29(22%) respondents reported that eyes should be examined ‘only when vision is affected’ and ‘every 6 months’ respectively, 98(74.2%) said the biggest barrier in getting eyes examined earlier was ‘lack of knowledge’, 23(17.4%) believed surgery was done for diabetic retinopathy treatment and 33(25%) believed that surgery, laser and injections all can be used. Significant relationship of diabetic retinopathy was found with duration of diabetes and the general health status (p<0.05). Conclusion: Though more than half the patients were aware that diabetes could affect the eyes, awareness of diabetic retinopathy and its consequences was low. Key Words: Awareness, Diabetes mellitus, Diabetic retinopathy, Continuous...